GREETING THOSE WHO HAVE BEEN LOST: REFLECTIVE PERSONAL PREACHING OF RELIGIOUS INSTRUCTORS IN THE POHUWATO EX-NAPITER CIRCLE - Arfan Nusi; Wisno Pakaya; Dian Adi Perdana (Universitas Islam Negeri Mataram, 2025)
This study aims to examine the effectiveness of the reflective personal preaching approach in the process of deradicalization and social reintegration of ex-terrorism convicts (ex-napiter) in Pohuwato Regency, Gorontalo Province. This approach emphasizes empathetic communication, spiritual guidance, and a humanizing reflection space. The method used is autoethnography, with the author as an Islamic religious instructor as well as a direct actor in the preaching process to seven ex-napiters. Data were obtained through in-depth interviews, participatory observations, and field notes. The results of the study indicate that reflective personal preaching is able to build trust, encourage ideological transformation, and strengthen the national spirit of ex-napiters. Through a preaching process that is not patronizing, but listens and touches on emotional aspects, ex-napiters begin to accept the values ??of religious moderation, play an active role in society, and demonstrate a commitment to living peacefully within the framework of the Republic of Indonesia. In conclusion, reflective personal preaching is effective as a humanitarian-based approach strategy in post-sentence deradicalization, and is relevant to be developed in the context of local-based extremism prevention.